The investigation of short-lived radionuclides for diagnosis of oncological diseases on the basis of practice in KazNRI of oncology and radiology - Abishev, M.E.; Nurshayeva, F.S. (Recent Contributions to Physics, 2017)
In the work on the criteria for selecting a radionuclide, short-lived radionuclides for PET, SPECT and for modern diagnostic methods for PET / CT and SPECT / CT were chosen. For each diagnostic method, radioisotopes, the type of decay, types of radiation, nuclear reactions, and decay energies were determined. For SPECT, calculations were carried out for the practical output of 99mTc from the generator during the lifetime from 20.10 to 3.11.2016 (15 days) in comparison with the theoretical (calculated) radioactivity. The volume and doses of the eluate preliminarily diluted with saline for the study of certain organs and systems were calculated. And for PET, short-lived radionuclides such as 11C, 13N, 15O, 18F, 82Rb were considered. Comparison of practical results with theoretical calculations is carried out. Some radiological parameters of radionuclides, widely used in radionuclide diagnostics, were also determined. They are presented in the main part of the article. Radionuclide diagnostics, thanks to its high efficiency, has become an indispensable part of clinical practice in developed countries. The use of such radiopharmaceuticals makes it possible to diagnose various diseases at early stages. To solve this problem and overcome dependence on imports, the Institute of Nuclear Physics of the NNC RK has been developing technologies for obtaining the most important medical isotopes and radiopharmaceuticals, such as sodium pertechnetate 99mTc, sodium iodide 131I, sodium o-iodophipate 131I, thallium chloride 201T1 and others . In the work, calculations of the decay energy were carried out and methods for registering the emissions were considered.